2010
DOI: 10.1007/s00403-010-1072-1
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol inhibits UVB-induced ROS generation and subsequent oxidative damage in cultured human skin dermal fibroblasts

Abstract: The exposure of cells to ultraviolet B radiation (UVB) can induce the production of reactive oxygen species (ROS) which damage cellular components. Free radical scavengers and antioxidants can interfere with the production of ROS. We studied cytotoxicity, intracellular ROS levels, lipid peroxidation, antioxidant status and oxidative DNA damage in cultured human skin dermal fibroblast adult cells (HDFa) exposed to UVB in the presence of sesamol, a natural phenolic compound. The levels of cytotoxicity, intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 56 publications
3
67
0
Order By: Relevance
“…Many experimental studies employing skin cells have demonstrated that UVB radiation can damage molecules and alter molecular structures, resulting in changes in cellular functions. 1,2) Recently, accumulating evidence has demonstrated that UVB-induced oxidative damage occurs through the generation of reactive oxygen species (ROS). 3,4) ROS, including singlet oxygen, hydrogen peroxide, superoxide anion, and hydroxyl radical play a critical role in UVBinduced oxidative stress.…”
mentioning
confidence: 99%
“…Many experimental studies employing skin cells have demonstrated that UVB radiation can damage molecules and alter molecular structures, resulting in changes in cellular functions. 1,2) Recently, accumulating evidence has demonstrated that UVB-induced oxidative damage occurs through the generation of reactive oxygen species (ROS). 3,4) ROS, including singlet oxygen, hydrogen peroxide, superoxide anion, and hydroxyl radical play a critical role in UVBinduced oxidative stress.…”
mentioning
confidence: 99%
“…8) In vitro, UVB radiation of human skin dermal fibroblasts stimulates intracellular production of reactive oxygen species (ROS). 9) Several lines of evidence suggest that ROS play important roles in mediating UV-induced cellular senescence by breaking DNA strands and modifying DNA bases. 2,10) Excess production and ineffective elimination of ROS production have thus been implicated in skin photoaging induced by UV radiation.…”
mentioning
confidence: 99%
“…In the skin dermis, reactive oxygen species (ROS) are produced in large amounts when UVB irradiation causes photoaging. These ROS cause lipid peroxidation, DNA damage, and oxidation of protein tissues (9). The peroxidation of lipids or the carbonylation of proteins would cause the skin to lose its resistance to photoaging and would accelerate the oxidative damaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increasing number of studies that have focused on the UV protective effects of food on skin to maintain healthy skin through diet. The food items that have been researched include green tea (6), red ginseng (7), mug-wort (8), and sesame oil (9).…”
Section: Introductionmentioning
confidence: 99%